Answer:
The answer is exactly two solutions.
Explanation:
The answer is exactly two solutions because Step: Solve3x+2y=6for x:
3x+2y=6
3x+2y+−2y=6+−2y(Add -2y to both sides)
3x=−2y+6
3x
3
=
−2y+6
3
(Divide both sides by 3)
x=
−2
3
y+2
Step: Substitute
−2
3
y+2forxin4x+5y=15:
4x+5y=15
4( −2 3 y+2)+5y=15
7
3
y+8=15(Simplify both sides of the equation)
7
3
y+8+−8=15+−8(Add -8 to both sides)
7
3
y=7
7
3
y
7
3
=
7
7
3
(Divide both sides by 7/3)
y=3
Step: Substitute3foryinx=
−2
3
y+2:
x=
−2
3
y+2
x=
−2
3
(3)+2
x=0 and y=3
Hope this helped.
x=0(Simplify both sides of the equation)